Evaluation of a rapid susceptibility test of polymyxin B by MALDI-TOF - Barth, Patricia Orlandi; Volpato, Fabiana Caroline Zempulski; Moreira, Natália Kehl; Wink, Priscila Lamb; de Souza, Ândrea Celestino; Barth, Afonso Luís (Frontiers in Microbiology, 2022)
Infections caused by multidrug-resistant microorganisms have become increasingly common in hospital environments around the world. Gram-negative bacilli stands out among multidrug-resistant bacteria mostly due to the production of carbapenemase enzymes which lead to resistance to most β-lactam antibiotics including the carbapenems. As a consequence, polymyxins have been reintroduced in the clinic as a last resort to treat infections caused by Gram-negative bacilli resistant to carbapenems. However, the only reliable method to evaluate the susceptibility to polymyxins is the broth microdilution, a laborious and time-consuming technique. Among infections caused by multidrug-resistant bacteria, bloodstream infections are the most worrisome as they can lead to sepsis and septic shock with high mortality rates. Considering the severity of sepsis and the need for a treatment guided for the susceptibility test in vitro, this work aimed to evaluate a rapid method of polymyxins susceptibility either from colonies grown on agar or directly from positive blood culture bottles using the technology of MALDI-TOF. The method was based on the “direct on target microdroplets growth assay” (DOT-MGA) originally developed by Idelevich and collaborators with some modifications (Adapted DOT-MGA). Isolates of Enterobacterales and non-fermenting gram-negative bacilli resistant to carbapenems were obtained from patients attending a tertiary care hospital in southern Brazil and tested as follows: 122 isolates from colonies grown on agar plates and 117 isolates directly from spiked positive blood cultures. The adapted DOT-MGA presented 95% and 100% of categorical agreement considering the colonies grown on agar plates and directly from positive blood cultures, respectively. The Adapted DOT-MGA test proved to be a reliable technique to evaluate the susceptibility to polymyxins to be used in microbiology laboratories with the MALDI-TOF equipment.